ELEMENTS OF SARCASM ON WILLY WONKA INTERNET MEMES - MUHAMMAD ADITYA PURNOMO, 121311233038 (2017)
Internet meme is one of popular object in internet. It is a combination between texts and images known as meme characters. The texts are then placed within upper and lower part of the image. Meme creators upload the memes they created and publish them using various meme publisher websites. There are various kinds of meme character with its own specific purposes. One of the purposes is to deliver sarcastic thoughts and humours. Sarcasm is a common occurence in conversation and generally known as implicit mock or insult targeted at a certain person. This study was conducted on a certain meme character specializes in delivering sarcastic thoughts: Willy Wonka. By applying the sarcasm cues theory as well as necessary sarcasm components compiled from various theorists, this study revealed the language use in Willy Wonka meme as well as its constructing components. The writer uses 10 Willy Wonka memes with the highest number of ‘likes’ from 9gag.com for this thesis. The sarcasm cue analysis showed that meme creators tend to use manner-violation cue in presenting their Willy Wonka memes in order to let the meme reader figure the actual meaning based on their own understanding. Necessary sarcasm component analysis found in Willy Wonka memes showed that manner-violation and hyperbole cue tend to be more successful in delivering sarcasm ideas compared to the other type of sarcasm cue.